A validated LC‐MS/MS method for the determination of canagliflozin, a sodium–glucose co‐transporter 2 (SGLT‐2) inhibitor, in a lower volume of rat plasma: application to pharmacokinetic studies in rats. (13th April 2016) - Kobuchi, Shinji; Yano, Kyoka; Ito, Yukako; Sakaeda, Toshiyuki
Abstract: Canagliflozin is a novel, orally selective inhibitor of sodium‐dependent glucose co‐transporter‐2 (SGLT2) for the treatment of patients with type 2 diabetes mellitus. In this study, a validated liquid chromatography–tandem mass spectrometry (LC‐MS/MS) method for the quantitative analysis of canagliflozin in a lower volume of rat plasma (0.1 mL) was established and applied to a pharmacokinetic study in rats. Following liquid–liquid extraction by tert ‐butyl methyl ether, chromatographic separation of canagliflozin was performed on a Quicksorb ODS (2.1 mm i.d. × 150 mm, 5 µm size) using acetonitrile–0.1% formic acid (90:10, v/v) as the mobile phase at a flow rate of 0.2 mL/min. The detection was carried out using an API 3200 triple‐quadrupole mass spectrometer operating in the positive electrospray ionization mode. Selected ion monitoring transitions of m/z  = 462.0 [M + NH4 ] +  → 191.0 for canagliflozin and m/z  = 451.2 [M + H] +  → 71.0 for empagliflozin (internal standard) were obtained. The validation of the method was investigated, and it was found to be of sufficient specificity, accuracy and precision. Canagliflozin in rat plasma was stable under the analytical conditions used. This validated method was successfully applied to assess the pharmacokinetics of canagliflozin in rats using 0.1 mL rat plasma. Copyright © 2016 John Wiley & Sons, Ltd.